Dopant-induced cationic bivalency in hierarchical antimony-doped tin oxide nano-particles for room-temperature SO2 sensing. Issue 38 (14th September 2021) - Chakraborty, Nirman; Ghose, Pradeepta Kumar; Rudra, Pratyasha; Das, Sagnik; Saha, Debdulal; Mishra, Ajay K.; Sanyal, Ambarish; Mondal, Swastik
Abstract : Antimony doping in tin oxide triggered generation of tin bivalency and it is the variation in ratio of 2+ and 4+ states of tin that determines the efficiency of room temperature SO2 sensing. Abstract : The modification of simultaneously existing multiple oxidation states in host lattice cations via the introduction of dopants has been reported for NiO- and Co3 O4 -based gas-sensing materials. However, SnO2, a widely used material for chemiresistive gas sensing has never been reported with simultaneous presence of Sn 2+ and Sn 4+ states, in both the absence and presence of dopants. In this work, we demonstrated how antimony doping in a 3+ state triggers the generation of cationic bivalency in tin oxide-based gas sensors, and it is the quantitative presence of unstable Sn 2+ species that determines the fate of SO2 -sensing responses by antimony-doped tin oxide gas sensors. While the Sn 2+ content in Sn0.856 Sb0.144 O2 is 1.2 times less than that of Sn0.957 Sb0.043 O2, the SO2 sensing response in the former is 1.2 times more than that in the latter. Greater antimony content in Sn0.856 Sb0.144 O2 also leads to the generation of additional trap states that result in sequential return of electrons back into the valence band. The reversibility of Sn 2+ ↔ Sn 4+ during SO2 adsorption and desorption brings out a new dimension of SnO2 -based chemiresistors besides those already existing.